2022
DOI: 10.1155/2022/6245647
|View full text |Cite|
|
Sign up to set email alerts
|

FSCN1 Promotes Glycolysis and Epithelial-Mesenchymal Transition in Prostate Cancer through a YAP/TAZ Signaling Pathway

Abstract: Objective. The aim of the study is to investigate the role and possible mechanism of fascin-1 (FSCN1) in the invasion, migration, glycolysis, and epithelial-mesenchymal transition (EMT) of prostate cancer. Methods. Real-time quantitative polymerase chain reaction (qRT-PCR) was utilized to determine the mRNA expression level of FSCN1 in prostate cancer tissues and prostate cancer cells PC-3 and DU145. The transwell and the scratch test were applied to detect the invasion and migration abilities of cells, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…97,98 Limited and hormone-refractory PCas show a significant upregulation of fascin-1 expression than that in benign prostate tissue. 6,68,69,99 In addition, a follow-up of patients undergoing radical prostatectomy has shown high fascin-1 expression to be related to an increased rate of PSA recurrence. 68 High fascin-1 expression is related to Gleason score and bone metastases, 69 thus confirming its role in PCa progression.…”
Section: Fascin-1 and Pcamentioning
confidence: 99%
See 3 more Smart Citations
“…97,98 Limited and hormone-refractory PCas show a significant upregulation of fascin-1 expression than that in benign prostate tissue. 6,68,69,99 In addition, a follow-up of patients undergoing radical prostatectomy has shown high fascin-1 expression to be related to an increased rate of PSA recurrence. 68 High fascin-1 expression is related to Gleason score and bone metastases, 69 thus confirming its role in PCa progression.…”
Section: Fascin-1 and Pcamentioning
confidence: 99%
“…70 Thus, targeting fascin-1 may be effective in preventing or treating metastatic PCa. 68,99,100 Octavian and Daniel et al investigated serum fascin-1 levels. 67,70 They showed that although serum fascin-1 levels differ in patients with and without PCa, the differences are not statistically significant.…”
Section: Fascin-1 and Pcamentioning
confidence: 99%
See 2 more Smart Citations
“…As a muscle-binding protein, FSCN1 plays a key role in cell migration, motility, adhesion, and cell-cell interactions. Furthermore, some studies have found that FSCN1 is aberrantly expressed in various cancers and is closely associated with the malignant behaviour of tumours [ 18 ].…”
Section: Introductionmentioning
confidence: 99%